A method for low-voltage electrical curing of cast-in-place ultra-high performance concrete

By adding conductive fillers to ultra-high performance concrete and adopting low-voltage electrical maintenance methods, the problems of high energy consumption and safety challenges in the prior art are solved, and the maintenance effect of the same or even higher strength as steam maintenance is achieved.

CN116283353BActive Publication Date: 2025-02-25SUZHOU CONCRETE CEMENT PROD RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310110842.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2025-02-25
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively replace the steam maintenance method of ultra-high performance concrete, and the electric maintenance method consumes high energy and has great safety challenges when it reaches the target temperature.

Method used

The low-voltage electrical curing method is adopted to add conductive fillers such as graphite and carbon nanotubes to ultra-high performance concrete, and use a constant voltage electrocuring device to enable efficient curing of concrete at a lower and constant voltage.

Benefits of technology

Ultra-high performance concrete achieves the same or even higher compressive strength of steam maintenance at low constant voltage, reducing energy consumption and investment in building steam maintenance chambers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116283353B_ABST
    Figure CN116283353B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for low-voltage electrical curing of cast-in-place ultra-high performance concrete, wherein the curing device used comprises a first electrode, a second electrode and a power supply device for providing a constant voltage, the cast-in-place ultra-high performance concrete is located between the first electrode and the second electrode, and the method comprises turning on the power supply device so that the power supply device continuously provides a constant voltage, wherein the raw material formula of the cast-in-place ultra-high performance concrete comprises cement, steel fiber, conductive filler, aggregate and admixture, the mass of the steel fiber is 20-30% of the mass of the cement, and the mass of the conductive filler is 1-5% of the mass of the cement. The present invention can obtain ultra-high performance concrete with the same or even higher strength as steam curing by curing specific cast-in-place ultra-high performance concrete at a relatively low constant voltage, thereby achieving the purpose of achieving an ideal strength of ultra-high performance concrete in a short period of time. Compared with steam curing, the present invention greatly saves energy consumption and the investment in building a steam curing room, and can be used as an alternative to steam curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a method for low-voltage electrical curing of cast-in-place ultra-high performance concrete. Background Art

[0002] Ultra-high performance concrete (UHPC) was developed in the 1990s. The high durability, post-hardening behavior and high strength have led to an increasing use of UHPC in construction projects. During the preparation of UHPC, in order to achieve a strength target of more than 120 MPa, the UHPC needs to be steam-cured at 90°C for several days. Although high temperature gradients in cement-based materials can cause cracks, the high density of UHPC and the addition of steel fibers with high flexural strength make UHPC very resistant to such cracks. However, steam curing requires large-scale manufacturing facilities and consumes a lot of energy.

[0003] Electrical curing is a relatively undeveloped alternative in the construction industry that generates heat through the Joule effect. Hardened concrete is normally non-conductive, but becomes conductive before reaching the final setting time. This is because concrete has a large amount of unreacted pore solution in the early stages, and the early resistivity is relatively low. As the concrete ages, cement hydration consumes the water inside, thereby increasing the resistivity and the hardened concrete gradually becomes an insulator. When electrical curing is performed on early concrete, the resistivity gradually increases due to the continuous dehydration of the concrete and the consumption of the hydration reaction. At this time, very high power is required to overcome the high resistivity of the concrete.

[0004] There is relatively little research on this method of electrical curing. The patent with application number 202210218383.4, "Electro-stimulation curing method and curing equipment for concrete structure in negative temperature environment", mentions measures for electrical curing in low temperature environment. This patent uses a constant power electro-stimulation method to electrically cure concrete at low temperature. This method can only raise the temperature of concrete to a maximum of 70°C, but fails to reach 90°C. In addition, this patent is mainly aimed at ordinary concrete, while ultra-high performance concrete is essentially different from ordinary concrete, that is, the water content is relatively low, the structure is denser, and the pore solution is also less. If the constant power method is used, in order to reach the set temperature, the initial power will be very large, which poses a greater challenge to safety. Yang Zhihan et al. also mentioned the method of electrical curing in the article "The Effect of Direct Electrical Curing on the Mechanical Properties of Concrete" published in the magazine "Concrete and Cement Products". This method uses a constant pressure method to electrically cure the concrete. However, during the curing process, the temperature of the concrete first rises and then drops, and the target temperature is maintained for a maximum of 4 hours. However, such a short curing time is not enough for the curing of ultra-high performance concrete and cannot achieve the effect of steam curing.

[0005] In summary, the current best curing method for ultra-high performance concrete is still steam curing, which has high curing costs. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for low-voltage electrical curing of cast-in-place ultra-high performance concrete in view of the deficiencies in the prior art, which can serve as an alternative to the steam curing method of cast-in-place ultra-high performance concrete, and the compressive strength of the cast-in-place ultra-high performance concrete after electrical curing reaches the same or even higher strength as that of steam curing.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for low-voltage electrical maintenance of cast-in-place ultra-high performance concrete, wherein the maintenance device used includes a first electrode, a second electrode, and a power supply device electrically connected to the first electrode and the second electrode and used to provide a constant voltage, and the cast-in-place ultra-high performance concrete is located between the first electrode and the second electrode. The method includes turning on the power supply device so that the power supply device continuously provides a constant voltage, wherein the raw material formula of the cast-in-place ultra-high performance concrete includes cement, steel fiber, conductive filler, aggregate and admixture, the mass of the steel fiber is 20-30% of the mass of the cement, and the mass of the conductive filler is 1-5% of the mass of the cement.

[0009] According to some implementation aspects of the present invention, the constant voltage is 5 to 40 V. Preferably, the constant voltage is 10 to 40 V. For example, the constant voltage is 20 V, 30 V, 40 V, etc.

[0010] According to some implementation aspects of the present invention, the constant voltage curing time is 8 to 48 hours, such as 8 hours, 12 hours, 24 hours, 48 ​​hours, etc.

[0011] According to some implementation aspects of the present invention, the conductive filler is graphite, carbon nanotubes, or a combination of the two.

[0012] Further, the conductive filler is a combination of graphite and carbon nanotubes in a mass ratio of 1:0.5 to 1.5. Preferably, the graphite and carbon nanotubes are in a mass ratio of 1:0.8 to 1.2. More preferably, the graphite and carbon nanotubes are in a mass ratio of 1:1.

[0013] In some embodiments, the particle size of the graphite is 600-1000 mesh. Preferably, the particle size of the graphite is 700-900 mesh.

[0014] In some embodiments, the carbon nanotubes are selected from single-walled carbon nanotubes and multi-walled carbon nanotubes, and have a diameter of 1 to 8 nm and a length of 0.1 to 5 μm.

[0015] According to some embodiments of the present invention, the first electrode and the second electrode are made of metal materials with good electrical conductivity, and further, the first electrode is made of copper or iron, and the second electrode is made of copper or iron. Preferably, the first electrode and the second electrode are made of iron respectively.

[0016] According to some embodiments of the present invention, the aggregate is selected from machine-made sand and quartz sand, and the admixture includes silica fume, silica powder and a water reducing agent.

[0017] In some embodiments, the raw material formula of the cast-in-place ultra-high performance concrete includes the following components: 25-35 parts of cement, 5-10 parts of water, 30-40 parts of aggregate, 5-10 parts of silica fume, 8-12 parts of silica powder, 0.5-3 parts of water reducer, 5-10 parts of steel fiber and 0.25-1.5 parts of conductive filler.

[0018] Preferably, the raw material formula of the cast-in-place ultra-high performance concrete includes the following components: 28-33 parts of cement, 6-9 parts of water, 30-35 parts of aggregate, 6-9 parts of silica fume, 9-12 parts of silica powder, 1-2 parts of water reducer, 6-8 parts of steel fiber and 1-1.5 parts of conductive filler.

[0019] In some embodiments, the method comprises the following steps:

[0020] (1) placing metal materials as a first electrode and a second electrode on two opposite sides of the mold;

[0021] (2) mixing all raw materials of cast-in-place ultra-high performance concrete, injecting into the mold and inserting the temperature sensor into the cast-in-place ultra-high performance concrete;

[0022] (3) The surface of the cast-in-place ultra-high performance concrete is covered with a film to prevent water loss, and a thermal insulation material is placed on the film;

[0023] (4) After pre-curing and demolding, the power supply device is electrically connected to the first electrode and the second electrode to apply a constant voltage for electrical curing, and the temperature sensor is electrically connected to a temperature measuring instrument to monitor temperature changes.

[0024] Furthermore, in step (3), the thermal insulation material is selected from polyurethane foam and polystyrene board. The thickness of the thermal insulation material is 10 to 20 cm.

[0025] Furthermore, in step (4), the pre-curing is performed in a standard box for 12 to 24 hours.

[0026] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0027] By using the method of the present invention to cure specific cast-in-place ultra-high performance concrete at a relatively low constant voltage, ultra-high performance concrete having the same or even higher strength as that obtained by steam curing can be obtained, thereby achieving the goal of achieving ideal strength of ultra-high performance concrete in a short period of time. Compared with steam curing, the method of the present invention greatly saves energy consumption and investment in building a steam curing room, and also shortens the service life of the mold, and can be used as an alternative to steam curing. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the structure of the curing device used in the method of the present invention;

[0029] In the figure: 1. first electrode; 2. second electrode; 3. temperature sensor; 4. temperature measuring instrument; 5. power supply equipment;

[0030] Figure 2 is a curve diagram of temperature and resistivity changes during electrical curing of ultra-high performance concrete of Example 1;

[0031] Figure 3 It is a curve diagram of the change of temperature and resistivity during the electrical curing of concrete in Comparative Example 1;

[0032] Figure 4 is a curve diagram of temperature and resistivity changes during electrical curing of ultra-high performance concrete of Example 2;

[0033] Figure 5 It is a curve diagram of the change of temperature and resistivity during the electrical curing of concrete in Comparative Example 2;

[0034] Figure 6 is a curve diagram of temperature and resistivity changes during steam curing of concrete in Comparative Example 4;

[0035] Figure 7 is a curve diagram of temperature and resistivity changes during steam curing of concrete in Comparative Example 5;

[0036] Figure 8 XRD curves of the concrete of Example 2, Comparative Example 2 and Comparative Example 5;

[0037] Fig. 9 In the figure, (a) is a simulation diagram of the formation of an internal conductive path in concrete of comparative example 1; (b) is a simulation diagram of the formation of an internal conductive path in ultra-high performance concrete of embodiment 1. DETAILED DESCRIPTION

[0038] Generally, steel fibers are added to the mix ratio of ultra-high performance concrete. As a one-dimensional conductive phase material, steel fibers can not only make ultra-high performance concrete have high strength, but also make ultra-high performance concrete itself conductive. In ultra-high performance concrete, steel fibers are connected with the pore solution to form a complete conductive path. However, as the hydration reaction proceeds, the water in the pores will gradually be consumed. The loss of water causes the conductive path to be blocked, thereby weakening the conductive properties of ultra-high performance concrete.

[0039] In order to improve the electrical conductivity of ultra-high performance concrete, the inventor of the present application tried to add finer fillers to ultra-high performance concrete. The inventor used carbon nanotubes as auxiliary conductive fillers in the present application by utilizing their excellent electrical conductivity (resistivity 1000 times lower than copper) and one-dimensional nanoscale geometry, and used granular graphite to further fill the gaps formed by one-dimensional filler steel fibers and carbon nanotubes, so that ultra-high performance concrete has a strong conductive path, and the strength of ultra-high performance concrete will not be reduced due to the addition of conductive fillers, and even higher strength can be obtained. Based on this, the inventor of the present application re-optimized the raw material formula of ultra-high performance concrete, so that it can achieve the purpose of direct electrical curing at a lower constant voltage, achieve the purpose of achieving ideal strength of ultra-high performance concrete in a short period of time, and obtain ultra-high performance concrete with the same or even higher strength as steam curing.

[0040] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0041] Example 1

[0042] The ultra-high performance concrete provided in this embodiment is composed of the following components, in parts by weight: 31 parts of silicate cement, 7.4 parts of water, 33 parts of machine-made sand, 7.9 parts of silica fume, 10.9 parts of silica powder, 1.6 parts of water reducer, 7 parts of steel fiber, 0.6 parts of graphite and 0.6 parts of carbon nanotubes.

[0043] in:

[0044] Portland cement is 52.5 cement;

[0045] The silica fume is Elkem 940U grade microsilica fume, with an average particle size of 0.2μm;

[0046] The average particle size of silicon powder is 4.2 μm;

[0047] The particle diameter of machine-made sand is 0.2-0.3mm;

[0048] The water reducing agent is BASF MELFLUX 4930F polycarboxylate water reducing agent, with a water reduction rate of 30%;

[0049] The graphite is flake graphite with a particle size of 800 mesh and a purity of 99%;

[0050] The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 1 to 8 nm and a length of 0.1 to 5 μm;

[0051] The curing method of ultra-high performance concrete in this example adopts a curing device such as Figure 1 As shown, it includes a first electrode 1, a second electrode 2 and a power supply device 5 electrically connected to the first electrode 1 and the second electrode 2 and used to provide a constant voltage. The cast-in-place ultra-high performance concrete is located between the first electrode 1 and the second electrode 2. The curing device also includes a temperature sensor 3 inserted into the cast-in-place ultra-high performance concrete and a temperature measuring instrument 4 connected to the temperature sensor 3 and used to monitor the internal temperature of the cast-in-place ultra-high performance concrete.

[0052] The method for low-voltage electrical curing of ultra-high performance concrete adopts the following steps:

[0053] (1) placing copper meshes as the first electrode 1 and the second electrode 2 on opposite sides of the mold;

[0054] (2) adding all raw materials into a mixer according to the raw material formula of ultra-high performance concrete, and mixing them evenly to obtain a mixture;

[0055] (3) Add the mixture into the mold of step (1), and then insert the temperature sensor 3 into the middle of the mixture;

[0056] (4) The surface of the mixture is covered with a film to prevent water loss, and a polyurethane foam insulation material with a thickness of 10 cm is placed on the film. The mold is placed in a standard curing box with a temperature of 20° C. and a humidity of 95% RH for curing for 1 day to obtain an ultra-high performance concrete test block;

[0057] (5) Demolding, connecting the first electrode 1 and the second electrode 2 at both ends of the test block to the power supply device 5, applying an AC voltage, and electrically curing the test block at a voltage of 20 V for 8 h. At the same time, turning on the multi-channel temperature measuring instrument 4 to monitor the temperature change, wherein the test frequency of the temperature measuring instrument 4 is 2 s / time;

[0058] (6) After the electrical curing is completed, the test block is placed in a standard curing box with a temperature of 20°C and a humidity of 95% RH for further curing. When the temperature drops to the ambient temperature, the strength of the test block is tested.

[0059] Example 2

[0060] The ultra-high performance concrete provided in this embodiment is basically the same as that in Embodiment 1, except that: in step (1), the first electrode 1 and the second electrode 2 are iron meshes; and in step (2), electrical curing is performed for 48 hours.

[0061] Example 3

[0062] The ultra-high performance concrete provided in this embodiment is basically the same as that in Embodiment 1, except that in step (2), the electrical curing constant voltage is 30V and the electrical curing is performed for 48 hours.

[0063] Example 4

[0064] The ultra-high performance concrete provided in this embodiment is composed of the following components by weight: 29 parts of silicate cement, 7.1 parts of water, 34.2 parts of machine-made sand, 8.7 parts of silica fume, 10.9 parts of silica powder, 1.7 parts of water reducer, 7.1 parts of steel fiber, 0.5 parts of graphite, and 0.8 parts of carbon nanotubes. The electrical curing method is the same as that in Example 1.

[0065] Comparative Example 1

[0066] The concrete provided in this example is basically the same as that in Example 1, except that the raw material formula of the concrete consists of the following components: 31 parts of Portland cement, 7.4 parts of water, 34.2 parts of machine-made sand, 7.9 parts of silica fume, 10.9 parts of silica powder, 1.6 parts of water reducer and 7 parts of steel fiber.

[0067] Comparative Example 2

[0068] The concrete provided in this example is basically the same as that in comparative example 1, except that the electrical curing time is 48 hours.

[0069] Comparative Example 3

[0070] The concrete provided in this example is basically the same as that in comparative example 1, except that the electrical curing constant voltage is 40V and the time is 48h.

[0071] Comparative Example 4

[0072] The concrete provided in this example is basically the same as that in Comparative Example 1, except that the concrete curing method adopts steam curing, and the specific steps are as follows:

[0073] (1) Add all raw materials into a mixer according to the raw material formula of concrete, mix them evenly, and prepare a mixture;

[0074] (2) Add the mixture into the mold, then insert the temperature sensor into the middle of the mixture, and place the mold in a standard curing box at a temperature of 20°C and a humidity of 95% RH for curing for 1 day to obtain a concrete test block;

[0075] (3) Remove the mold, place the test block in a steam curing box, adjust the temperature of the steam curing box to 95°C, steam cure for 48 hours, and turn on the multi-channel temperature measuring instrument to monitor the temperature change. The test frequency of the temperature tester is 2 seconds / time;

[0076] (4) After steam curing, the test block was placed in a standard curing box at a temperature of 20°C and a humidity of 95% RH for further curing. When the temperature dropped to ambient temperature, the strength of the test block was tested.

[0077] Comparative Example 5

[0078] The concrete provided in this example is basically the same as that in Example 1, except that the curing method of the concrete adopts steam curing, and the specific steps are as follows:

[0079] (1) Add all raw materials into a mixer according to the raw material formula of concrete, mix them evenly, and prepare a mixture;

[0080] (2) Add the mixture into the mold, then insert the temperature sensor into the middle of the mixture, and place the mold in a standard curing box at a temperature of 20°C and a humidity of 95% RH for curing for 1 day to obtain a concrete test block;

[0081] (3) Remove the mold, place the test block in a steam curing box, adjust the temperature of the steam curing box to 95°C, steam cure for 48 hours, and turn on the multi-channel temperature measuring instrument to monitor the temperature change. The test frequency of the temperature tester is 2 seconds / time;

[0082] (4) After steam curing, the test block was placed in a standard curing box at a temperature of 20°C and a humidity of 95% RH for further curing. When the temperature dropped to ambient temperature, the strength of the test block was tested.

[0083] Comparative Example 6

[0084] The ultra-high performance concrete provided in this comparative example is composed of the following components by weight: 33 parts of silicate cement, 7.4 parts of water, 31.2 parts of machine-made sand, 8.1 parts of silica fume, 10.7 parts of silica powder, 2 parts of water reducing agent, 7 parts of steel fiber, 0.2 parts of graphite, and 0.4 parts of carbon nanotubes. The electrical curing method is the same as that of Example 1.

[0085] The mechanical properties of the concrete of Examples 1 to 4 and Comparative Examples 1 to 6 were tested in accordance with GB / T50081-2019 standard, and the results are shown in Table 1. The temperature and resistivity of the concrete of Examples 1 to 2 and Comparative Examples 1 to 2 and Comparative Examples 4 to 5 during the curing process were monitored, and the results are shown in Table 1. Figures 2 to 7 As shown; XRD test was performed on the concrete of Example 2, Comparative Example 2 and Comparative Example 5, and the results are as follows Figure 8 shown.

[0086] Table 1 shows the performance test results of concrete of Examples 1 to 4 and Comparative Examples 1 to 6

[0087]

[0088]

[0089] Electrical conduction can be divided into ionic conduction and electronic conduction. Ionic conduction occurs due to the movement of ionic charges while electronic conduction is caused by the movement of electrons in response to an electric field. Furthermore, an increase in the number of charges to be transferred results in an increase in temperature.

[0090] Figure 2 is a curve diagram of temperature and resistivity changes during electrical curing of ultra-high performance concrete of Example 1; Figure 3 The temperature and resistivity curves of the concrete during electrical curing of Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the resistivity of concrete changes significantly during the electrical curing process, indicating that ionic conduction is the main conduction mechanism of concrete even with the addition of steel fibers. Before the start of curing, the concrete matrix is ​​full of water, and the ions in the water can transfer charges between the steel fibers, so the resistivity of the concrete is the lowest at this time. Then, as the curing progresses, the number of water ion charges transferred decreases due to the consumption of water during the hydration reaction and the evaporation of water during the heating process, which weakens the strength of the conductive path in the matrix. Therefore, as the electrical curing progresses, the resistivity of the concrete increases sharply, and the low voltage of 20V is not enough to increase the temperature of the concrete, so the temperature of the matrix begins to decrease. In contrast, for concrete doped with carbon nanotubes and graphite, since the carbon nanotubes and graphite are evenly distributed throughout the matrix, and they are intricately connected to the steel fibers in the matrix, they constitute a strong conductive path controlled by electronic conduction regardless of the water content. Therefore, Figure 2 It can be seen that as the electrical curing progresses, the resistivity of the test block increases slightly in the initial stage. As the temperature increases, the activation energy of the test block increases, so that the resistivity of the test block decreases slightly again, and then the resistivity remains stable.

[0091] Figure 8The XRD curves of the test blocks of different cases are measured after the hydration is terminated immediately after the electrical curing is completed. Comparing the XRD curves of Comparative Example 2 and Example 2, it can be seen that the peak intensity of Ca(OH)2 in Example 2 is significantly stronger than that of Comparative Example 2. This is because Comparative Example 2 is a concrete without carbon nanotubes and graphite added, and the initial resistivity of the test block is relatively high. The voltage of 20V is not enough to raise its temperature to 90°C. As the temperature rises and the hydration of the test block accelerates, the water content in the test block gradually decreases, thereby further increasing the resistivity of the test block and the temperature of the test block begins to decrease. This process does not significantly increase the degree of hydration of the test block. For the test block with added carbon nanotubes and graphite (Example 2), the initial resistivity is relatively low, and the carbon nanotubes, graphite and carbon fiber form a strong conductive path, so that the voltage of 20V can raise the test block to 90°C within 2 hours. Due to the existence of the strong conductive path, the resistivity of the test block will not increase with the evaporation of the water in the test block and the increase in the degree of hydration, so that the test block can be maintained at 90°C until the end of electrical curing. This process effectively ensures the hydration speed and degree of the test block, so that in the XRD curve, the intensity of the Ca(OH)2 peak is significantly higher than that of Comparative Example 2.

[0092] Table 1 shows the strength of the test blocks under different curing systems. It can be seen from Table 1 that the strength of the concrete with carbon nanotubes and graphite added (Example 2) after 48 hours of electrical curing is 157.25Mpa. Compared with the strength of the test block after steam curing of 152.89Mpa, the strength of electrical curing is 3% higher than the strength of steam curing. It proves that electrical curing can achieve the effect of steam curing or even better than the effect of steam curing. And under the same curing system, the strength of the test blocks with carbon nanotubes and graphite added (Examples 1-2) is higher than that of conventional concrete (Comparative Examples 1-2). This is because in addition to providing a strong conductive path for concrete, carbon nanotubes and graphite can also utilize their size effect, which can play a good physical filling effect, optimize the pore structure of the conductive mortar, and thus improve the mechanical strength of the conductive mortar; in addition, carbon nanotubes and graphite can also serve as crystal nuclei to promote the hydration of cement-based materials. Therefore, the strength of concrete with carbon nanotubes and graphite added is higher than that of conventional concrete.

[0093] Fig. 9 A simulated diagram of the conductive path formed in concrete. Fig. 9 (a) It can be seen that for ordinary concrete without adding carbon nanotubes and graphite, the conductive path mainly relies on steel fibers and pore water solution. However, as the temperature rises during the curing process and the water is consumed during the hydration reaction, the conductive path will be forced to interrupt, and the conductivity of the concrete will drop sharply. Fig. 9(b) It can be seen that for concrete with added carbon nanotubes and graphite, the formation of the conductive path mainly depends on the interconnection of steel fibers, carbon nanotubes and graphite. The effect of moisture on the conductivity of this type of concrete is minimal. Therefore, with the increase of temperature and the consumption of moisture during the hydration reaction, the resistivity of the concrete can be maintained at a low level. A low level of resistivity is a prerequisite for low-voltage electrical maintenance of concrete.

[0094] In the present invention, even at a low voltage of 20V, the temperature of the substrate can be raised to 90°C, and the electrical curing can produce an effect similar to or even higher than that of steam curing. For Example 2, after 48 hours of electrical curing, the strength was increased by 3% compared with steam curing. This shows that electrical curing exhibits similar or even higher mechanical properties than steam curing. The results of the present invention indicate the possibility of electrical curing of cast-in-place ultra-high performance concrete under field conditions. For prefabricated ultra-high performance concrete products, as an alternative to steam curing, high efficiency and energy saving of electrical curing can be achieved by adding an appropriate amount of carbon nanotubes and graphite to the ultra-high performance concrete products to reduce the resistivity of the concrete products. In this way, even low voltage can fully increase the temperature of the target product.

[0095] For reinforced UHPC products and products that have metal mesh arranged on them, it may be easier than expected to apply electrical curing to the UHPC on site with the help of existing steel bars or metal mesh, which can act as electrodes without adding additional metal electrodes. The specific method is to expose both ends of the steel bars or metal mesh on the surface of the structure, which can be connected to a power source. Heat can be generated in the steel bars or metal mesh by Joule heating and diffused into the concrete structure. Even if the length of the steel bars or metal mesh is long, the temperature stress caused by the temperature difference can become negligible and controllable due to the excellent thermal properties of the steel bars or metal mesh and the ultra-high strength of the UHPC. When the electrical curing process is completed, the exposed steel bars or metal mesh can be cut off. In this way, electrical curing is feasible. In addition, since the UHPC product reaches the target strength earlier, this method can shorten the construction time.

[0096] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0097] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for low-voltage electrical curing of cast-in-place ultra-high performance concrete, wherein the curing device comprises a first electrode, a second electrode, and a power supply device electrically connected to the first electrode and the second electrode and used to provide a constant voltage, and the cast-in-place ultra-high performance concrete is located between the first electrode and the second electrode, characterized in that: The method comprises turning on the power supply device so that the power supply device continuously provides a constant voltage, wherein the raw material formula of the cast-in-place ultra-high performance concrete comprises cement, steel fiber, conductive filler, aggregate and admixture, the mass of the steel fiber is 20-30% of the mass of the cement, and the mass of the conductive filler is 1%-5% of the mass of the cement; the raw material formula of the cast-in-place ultra-high performance concrete comprises the following components: 25-35 parts of cement, 5-10 parts of water, 30-40 parts of aggregate, 5-10 parts of silica fume, 8-12 parts of silica powder, 0.5-3 parts of water reducer, 5-10 parts of steel fiber and 1.2-1.5 parts of conductive filler; The constant voltage is 5 to 30V; The curing time is 8 to 48 hours; The conductive filler is a combination of graphite and carbon nanotubes in a mass ratio of 1:0.8 to 1.2; The particle size of the graphite is 600-1000 mesh; The carbon nanotubes are selected from single-walled carbon nanotubes and multi-walled carbon nanotubes, and have a diameter of 1 to 8 nm and a length of 0.1 to 5 μm; The first electrode and the second electrode are copper mesh or iron mesh.

2. The method for low-voltage electrical maintenance of cast-in-place ultra-high performance concrete according to claim 1, characterized in that: The aggregate is selected from machine-made sand and quartz sand.

3. The method for low-voltage electrical maintenance of cast-in-place ultra-high performance concrete according to claim 1, characterized in that: The admixture comprises silica fume, silica powder and a water reducing agent.

4. The method for low-voltage electrical maintenance of cast-in-place ultra-high performance concrete according to claim 1, characterized in that: The method comprises the following steps: (1) placing metal materials as a first electrode and a second electrode on two opposite sides of the mold; (2) mixing all raw materials of cast-in-place ultra-high performance concrete, injecting into the mold and inserting the temperature sensor into the cast-in-place ultra-high performance concrete; (3) The surface of the cast-in-place ultra-high performance concrete is covered with a film, and a thermal insulation material is placed on the film; (4) After pre-curing and demolding, the power supply device is electrically connected to the first electrode and the second electrode to apply a constant voltage for electrical curing, and the temperature sensor is electrically connected to a temperature measuring instrument to monitor temperature changes.

Citation Information

Patent Citations

  • Negative temperature environment concrete structure electrical excitation curing method and curing equipment thereof

    CN114278107A